On religious toleration for criminals - Gibson, Edward (Statistical and Social Inquiry Society of Ireland, 1867)
My object is indicated by the title of my paper. I wish for an enquiry into the extent and limits of religious toleration afforded to criminals in Ireland. It is not many years since the Protestant prisoner alone was permitted to receive the ministrations of his clergy within the walls of that jail in which, if the criminal should be punished, he should assuredly be permitted, after his own fashion, to pray to his God for penitence. That exclusive system was abandoned in deference to the imperious demand of a more enlightened age, and now the doors of the Irish convict prisons are freely open to admit Roman Catholic and Presbyterian chaplains. But there are other forms of religious belief besides the Protestant, the Roman Catholic, and Presbyterian; and there are, unfortunately, some who have no belief at all; and my present object is to draw attention to the discipline to which those who do not conform to any of the favoured religions are subjected in the convict prisons of Ireland.
Read Tuesday, 21st May, 1867
Keywords: Penal system; Religious belief; 314.15